Calcium carbonate production by fish in temperate marine environments. (1st October 2019) - Salter, Michael A.; Perry, Chris T.; Smith, Abigail M.
Abstract: Marine bony fishes are an important source of calcium carbonate with relevance to sediment production and inorganic carbon cycling. However, knowledge of the production and fate of these carbonates is based primarily on data from warm‐water reef fishes, with efforts to assess global‐scale implications constrained by assumptions that this small cross section of the global fish community is widely representative. Here we test the extent to which temperature influences fish carbonate mineralogy and morphology by comparing products from temperate settings (20 species at temperatures spanning 10–18°C) against existing data (23–27°C). Overall, carbonate products were mineralogically, compositionally, and morphologically similar throughout the thermal range, and in most cases, we observed no differences within species (18 vs. 24°C) or families (10 vs. 25°C). Confirmation of within‐family consistency over large thermal gradients is significant because: (1) it facilitates a substantial range expansion over which fish carbonate production models can be constructed, even where family‐level product data are geographically limited; and (2) it implies that the solubility of products from any given fish family varies only due to local carbonate saturation states at excretion (and not crystallographic differences). The only exception was in two members of the Labridae (wrasses), which produced low‐Mg calcite (LMC) and minor amorphous calcium–magnesium carbonate (ACMC) at 10°C; the inverse of products from confamilials at 25°C. This finding could have significant implications for understanding the role of fish carbonates globally because ACMC is a highly unstable carbonate polymorph, whereas LMC is very stable.